Delineating protection areas for caves using contamination vulnerability mapping techniques: the case of Herrerı´as Cave, Asturias, Spain - Marín-Guerrero, Ana Isabel; Andreo-Navarro, Bartolomé; Jiménez-Sánchez, Montserrat; Domínguez-Cuesta, María José; Meléndez-Asensio, Mónica; Meléndez Asensio; Marín-Guerrero, Ana Isabel (National Speleological Society, 2012)
Diverse approaches are adopted for cave protection. One approach is delineating protection areas with regard to their vulnerability to contamination. This paper reports the main results obtained from the delineation of a protection zone for Herrerı´as Cave, declared of Cultural Interest by the Asturias Regional Government, based on assessing its vulnerability to contamination. The cave is situated in a complex karst hydrogeologic environment in which groundwater flows from southwest to northeast, following the bedrock structure. A stream flows inside the cave, emerging in a spring located to the northeast of the system. Karst recharge occurs by direct infiltration of rainfall over limestone outcrops, concentrated infiltration of surface runoff in the watershed draining the cave, and deferred infiltration of water from alluvial beds drained by influent streams. The soil and vegetation covers are natural in the majority of the test site, but land uses in the watershed, including scattered farming, stock breeding, quarrying, and tourist use, are changing the natural characteristics and increasing the cave’s vulnerability to contamination. The procedure followed for delineating protection zones is based on the method COP+K that is specifically designed for vulnerability mapping of groundwater springs in carbonate aquifers. To cover the hydrological basin included in the cave’s catchment area, the protection zones established includes two different areas, the hydrogeological catchment basin and adjacent land that contributes runoff. Different degrees of protection in the zones have been proposed to make human activity compatible with conservation of the cave, and our results show remarkable differences from the protection zone previously proposed for the same area
Keywords: Cuevas - Protección; Cave; Protection; COP method; Cueva de la Herrería; Contaminación